2020
DOI: 10.1039/d0re00191k
|View full text |Cite
|
Sign up to set email alerts
|

An automated flow platform for accurate determination of gas–liquid–solid reaction kinetics

Abstract: An automated flow platform based on tube-in-tube contactor and micropacked bed reactor is developed to measure the kinetics of gas-liquid-solid hydrogenation reactions. The liquid flowing in the inner tube of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…As these tools continuously measure the reaction medium, this allows a high data density to be obtained, which can be particularly useful when utilising the flow rate manipulations discussed within this review. [46][47][48][49][50] However, the use of PAT alone for kinetic analysis can be challenging, as there are often multiple interfering components within the reaction medium that result in difficulties obtaining the quantitative information necessary for modelling. 51 These challenges can be overcome in some cases using multivariate modelling, 47 but the high level of expertise necessary for this task results in many researchers utilising online, discrete sampling methods instead.…”
Section: Reaction Chemistry and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…As these tools continuously measure the reaction medium, this allows a high data density to be obtained, which can be particularly useful when utilising the flow rate manipulations discussed within this review. [46][47][48][49][50] However, the use of PAT alone for kinetic analysis can be challenging, as there are often multiple interfering components within the reaction medium that result in difficulties obtaining the quantitative information necessary for modelling. 51 These challenges can be overcome in some cases using multivariate modelling, 47 but the high level of expertise necessary for this task results in many researchers utilising online, discrete sampling methods instead.…”
Section: Reaction Chemistry and Engineeringmentioning
confidence: 99%
“…As the analytical time is also decoupled from the residence time, it was shown by Hone et al that 3 minute HPLC methods could be run with only 15 seconds difference in each sampled residence time, which would otherwise not be possible in batch. 38 Since the original publication, controlled ramp experiments have been reported many times in the literature due to their experimental advantages, 50,[55][56][57][58] i.e. reduced material consumption, precise and reproducible kinetic profiling, etc.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Several approaches have previously been reported for assessing the amounts of dissolved gasses in continuous flow gas-liquid systems. [18][19][20][21] We elected to employ two approaches. In the first instance a bubble counting technique that uses computer vision was employed to estimate the amount of gassing out as the reaction stream exited the reactors BPR.…”
Section: Assessment Of the On-the-fly Removal Of Ozone Gasmentioning
confidence: 99%
“…11 Therefore, these studies revealed that continuous flow microreactors provide excellent gasliquid mass transfer to accelerate the rate of mass-transfer limited reactions. Additionally, microreactors represent an attractive tool for kinetics measurements, [20][21][22] owing to their excellent mixing performance and improved process control. According to the published works, 11,23,24 the kinetics of Cu/ TEMPO-catalyzed aerobic alcohol oxidation is very complicated.…”
Section: Introductionmentioning
confidence: 99%